Detachable smart teaching device for the easy and safe operation of robot manipulator - Do, Hyunmin; Kim, Hwi Su; Kim, Uikyum; Choi, Tae Yong; Park, Jongwoo (RO-MAN 2022 - 31st IEEE International Conference on Robot and Human Interactive Communication: Social, Asocial, and Antisocial Robots, 2022)
Increasing demand for automation and recent intact trends have accelerated the employment of robots in manufacturing and service areas. Thus, there is a growing demand for easier and safer operation of robots, both by experts and non-professionals. This paper proposes a detachable smart robot teaching device with collision prediction to meet such demands. The proposed device is composed of two modules. One is for easy teaching based on a 6D mouse, and the other is for safe operation by measuring the distance to the surrounding obstacles and predicting the collision situation. The teaching module is used only in a teaching phase and can be separated afterward. A prototype is implemented, and the performance is verified through experiments with a collaborative robot.
Keywords: Collision prediction; Growing demand; Performance; Robot teaching; Robots manipulators; Safe operation; Service area; Smart robots; Surrounding obstacles; Teaching module